Chemistry in the Laboratory - Hunter, Paul (Okemos Press, 2006)
This handout will include information about: Changing sections, Checking out and checking in your equipment, What to do if you miss your laboratory class, Your prelab problem sets, Your final examination, Where to get assistance, How your grade will be determined, The instroductors and the staff for the course :